The effects of foot orthoses on radiological parameters and pain in children with flexible flat feet: a systematic review and meta-analysis - Liu, Chao; Zhang, HongHao; Li, JianPing; Li, ShiJia; Li, GuQiang; Jiang, XiangZhan (Frontiers in Pediatrics, 2024)
Objective: This study aimed to investigate the impact of foot orthoses on foot radiological parameters and pain in children diagnosed with flexible flatfoot. Methods: A comprehensive search was conducted across several databases, including PubMed, Web of Science, EMBASE, Cochrane Library, and EBSCO, covering publications from the inception of each database up to 8 June 2024. The study focused on randomized controlled trials investigating the use of foot orthoses for treating flexible flat feet in children. Four researchers independently reviewed the identified literature, extracted relevant data, assessed the quality of the studies, and performed statistical analyses using RevMan 5.4 software. Results: Six studies involving 297 participants were included. The methodological quality of the included literature ranged from moderate to high. Radiological parameters of the foot improved significantly in older children with flexible flat feet following foot orthotic intervention compared to controls, particularly in the lateral talar-first metatarsal angle ( mean difference (MD)= -2.76, 95% confidence interval (95% CI ) -4.30--1.21, p = 0.0005), lateral talo-heel angle (MD = -5.14, 95% CI -7.76 --2.52, p = 0.0001) and calcaneal pitch angle (MD = 1.79, 95% CI 0.88-2.69, p = 0.0001). These differences were statistically significant. Additionally, foot orthoses significantly improved the ankle internal rotation angle and reduced foot pain in children with symptomatic flexible flatfoot (MD = -2.51, 95% CI -4.94 --0.07, p = 0.04).The use of foot orthoses positively impacts the improvement of radiological parameters of the foot and reduces pain in older children with flexible flat feet. However, in younger children with flexible flat feet, the improvement from foot orthoses was not significant, likely due to challenges in radiological measurements caused by the underdevelopment of the ossification centers in the foot. Further studies are needed. Consequently, the results of this meta-analysis support the implementation of an early intervention strategy using foot orthoses for the management of symptomatic flat feet in older children.